STRATEGI PROMOSI PERPUSTAKAAN KHUSUS SEBAGAI TEKNIK MARKETING DI PERPUSTAKAAN KANTOR PERWAKILAN BANK INDONESIA PROVINSI BALI TAHUN 2023 - Maharani, Luh Ade Angguningtyas; Haryanti, Ni Putu Premierita; Suhartika, I Putu (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 4 No 1 (2024), 2024)
Libraries need to conduct persuasive promotions to attract users and potential users to visit and optimally utilize available services. To achieve the goal of library promotion, the library needs to have a promotion strategy, which is the steps taken to achieve a certain goal. This research focuses on the Perpustakaan KPw. Bank Indonesia Provinsi Bali, a special library that is also open to the general public which based on observation shows that the number of general public visitors to the library has increased significantly since the promotion during 2023. This paper utilizes a qualitative research method with a descriptive study. Data collection were conducted using observation, interview, and literature study techniques. The results showed that Perpustakaan KPw. Bank Indonesia Provinsi Bali has implemented a promotional strategy that includes internal and external promotions to attract visitors to the library. Internal promotion at the Perpustakaan KPw. Bank Indonesia Provinsi Bali is aimed at internal staff, while external promotion to attract external visitors is done through social media, personal selling, and special events.